Significance of Bishop score in single vs. double balloon catheterization for induction in labor; a meta-analysis - Wang, Ping; Hu, Yan; Shan, Tengfei; Fang, Fei (Frontiers in Surgery, 2025)
ObjectiveTo conduct a meta-analysis comparing Bishop scores in newborns resulting from single balloon versus double balloon labor induction methods.MethodsWe performed a meta-analysis of RCT's that compared single and double balloon catheters for inducing labor. Relevant literature studies were located by searching PubMed, MEDLINE, EMBASE, and the Cochrane Library. The primary outcome measure was the Bishop score, while secondary outcomes included the mode of delivery, complications, time interval from catheter insertion to the delivery, and the Apgar score at five minutes.ResultsOur meta-analysis encompassed 6 RCT involving 996 women who underwent labor induction. We detected a substantial variation in the Bishop scores, with SBC induction yielding higher scores. Specifically, neonates delivered using SBC had higher Bishop scores than those delivered using DBC. This highlights the clinical significance of Bishop scores in identifying infants who may require immediate medical attention. However, no significant differences were found in mode of delivery, complications, or Apgar scores between the two groups (P > 0.05).ConclusionLabor induction using a single balloon catheter appears to be more effective at ripening the cervix, as indicated by higher Bishop scores. This suggests that it might be a more favorable method for inducing labor.